Recent clinical and pharmacological advancements of incretin-based therapy and the effects of incretin on physiology - Bhaskar Pal; Moitreyee Chattopadhyay (Journal of Diabetology)
A novel therapeutic target for diabetes mellitus is incretin-based therapies, glucagon-like peptide-1, and glucose-dependent insulinotropic polypeptides are released from the gastrointestinal (GI) tract and act on beta cells of pancreatic islets by increasing the secretion of insulin. The management and prevention of diabetes require habitual and pharmacological therapies along with quality and healthy lifestyle. This includes maintaining the body weight, blood glucose level, cardiovascular risk, complexity, and co-morbidities. The utilization of glucagon-like peptide-1 (GLP-1) agonists is an object of research with favorable hemoglobin A1C levels and weight loss in type 1 diabetic patients. However, cost-effectiveness and tolerability, remain significant barriers for patients to using these medications. The risk of suicidal tendencies and thoughts of self-harm have been increased in patients receiving GLP-1 receptor agonists. Tirzepatide treatment showed a potent glucose-lowering effect and promoted weight loss with minimum GI adverse effects in animal studies as well as phase I and II human trials, in comparison with established GLP-1 receptor agonists. The glucose-dependent insulinotropic polypeptide receptor (GIPR) peptide-antagonist effectively blocks the action of gastric-inhibitory-polypeptide (GIP) in vitro and ex vivo in human pancreas and in vivo in rodent models. However, incretin-based therapies have received enormous attention in the last few decades for the treatment of diabetes, obesity, and other repurposing including central nervous system disorders. Therefore, in this article, we demonstrate the overview, physiological, and pharmacological advances of incretin-based pharmacotherapies and their physiological roles. Furthermore, the recent updates of glucagon-like peptide-1 receptor agonist, Glucagon-like peptide-2 receptor agonist, GLP-1/GIP co-agonists, GIP/GLP-1/glucagon triple agonist and GIP-antagonist are also discussed.